Related factors of periodontal health among Chinese middle school students, findings from a national cross-sectional survey - Jingyu Zhan; Yu Zhang; Xing Wang; Baojun Tai; Deyu Hu; Huancai Lin; Bo Wang; Yan Si; Chunxiao Wang; Shuguo Zheng; Xuenan Liu; Wensheng Rong; et al. (BMC, 2021)
Abstract Background To investigate the related risk factors of periodontal health status among Chinese middle school students. Methods This study is a part of the Fourth National Oral Health Epidemiological Survey, which is by far the largest oral epidemiological survey in China, including all provinces, municipalities and autonomous regions in mainland China. A multi-stage stratified sampling method was used to select middle school students aged 12-15 from the sampled middle school for investigation. The survey consisted of two parts: oral examination and questionnaire survey. The oral examination included gingival bleeding and calculus. The questionnaire included sociodemographic information, oral health knowledge, attitudes and behaviors. Logistic regression and generalized linear mixed model were used to investigate the risk factors of gingival bleeding and calculus. Results A total of 118,514 middle-school students has been examined. Less gingival bleeding (OR = 0.746, CI 0.718-0.774) and calculus (OR = 0.550, CI 0.529-0.527) were found in 12-year-old group compared to 15-year-old group. The periodontal health status of males was worse than that of females (gingival bleeding OR = 1.102, CI 1.074-1.132, calculus OR = 1.258, CI 1.223-1.295). Besides age and gender, region, living place, ethnic groups, family structure, parent's education level, oral health knowledge and behavior were also related to gingival bleeding and calculus. Conclusions Gingival bleeding and calculus occurred most of 12-15 years old adolescents in China. Several related factors, such as gender, age, ethnicity, father's education level, oral health knowledge and behavior, were found in multi-factorial models. The impact of province should arouse people's attention.